(untitled) - Lam, Thị Hoa Binh (Ha Noi, 2006)
EGEO aims at providing a background knowledge of economic and natural geography in english for students though a combination of texts, diagrams and interesting illustrations with many exercises, grammar exercises, oral work, discussion and translation.
Keywords: Geography,Địa lý; Study and teaching,Dạy học